Pengaruh Model Pembelajaran PBL (Problem Based Learning) pada Materi Perubahan Lingkungan terhadap Kemampuan Literasi Sains dan Motivasi Belajar Peserta Didik Kelas X SMA Negeri 2 Magelang: (The Influence of the PBL (Problem Based Learning) Learning Model on Environmental Change Material on the Science Literacy Ability and Learning Motivation of Class X Students of SMA Negeri 2 Magelang) - Pujiyanti, Nastiti Rahayu; Darmawan, Ericka; Permadani, Karunia Galih (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
Based on observations made at SMA Negeri 2 Magelang, the learning carried out at school still uses the Teacher Centered Learning (TCL) model, this causes the ability of science literacy and students' motivation in learning to be not optimal. This study aims to measure the influence of the PBL model on science literacy skills with indicators according to PISA (2022) on aspects of knowledge and learning motivation with Hamzah (2013) indicators. The type of research used is quantitative research with a quasi experiment method of Pretest Post-test Non Equivalent Control Group Design and the sampling technique is purposive sampling. The sample used in this study is class X-3 an experimental class with 36 people and class X-5 a control class with 36 people. The data on science literacy ability showed that the average pretest score of the control class was 44.37 and the average post-test score was 65.43, while for the experimental class, the average pretest score was 43.26 and the average post-test score was 79.34. In the data on learning motivation ability, the average pretest score of the control class was 75.03 and the average post-test score was 76.89, while for the experimental class, the average pretest score was 75.31 and the average post-test score was 83.34. The asym sig value (2-tailed) is 0.000<0.05, the hypothesis test shows that the PBL model affects science literacy and students’ learning motivation. Key words: PBL, Science Literacy, Motivation, Environmental Change